Role of Chest Radiography in Diagnosing Pulmonary Tuberculosis, Does Every Suspected Case Needs GeneXpert MTB; A Cross-Sectional Study - Mujahid Raza; Saleh Khurshied; Altaf Hussain; Nawal Khurshid; Ali Khurshid (Pakistan Journal of Medical Research, 2025)
Background: Pulmonary tuberculosis (TB) triggers a common infection globally. Chest X-ray (CXR) plays a role in diagnosis of pulmonary TB and has typical findings. CXR is cost effective modality and can help to reduce the burden on health system if smear, culture, or rapid molecular tests are only done in patients where CXR shows suspicion of pulmonary TB.